Digitalisasi Informasi dan Peningkatan Kualitas Pelayanan Publik Transformasi Desa Digital Melalui Pengembangan Website Desa Klatakan - Ida Fitriana Ambarsari; Nur Azizah; Ansori Ansori; Yuski Fausi Al-faruq; Kavel Kafabi Fahrozi (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The transformation of villages into digital villages through the development of village websites is an important step in improving the quality of public services at the local level. This article reviews the impact of information digitization in the context of Klatakan Village website development on improving the quality of public services. Through the village website, the community can access information about development programs, health services, education, and community activities more quickly and easily. The use of digital technology allows villages to communicate effectively with their citizens, increase transparency, and speed up responses to community input. However, the success of the digital village transformation also depends on the internet accessibility and digital literacy of the community. Therefore, the government needs to ensure adequate digital infrastructure and provide training for residents to optimally utilize the village website. Thus, the development of the Klatakan Village website can serve as an example of how information digitization can improve the quality of public services at the village level and strengthen community participation in local development.